Implementation of the Rantang Simpati Program and Its Implications for Public Social Education - Eti Setiawati; Indriyati Kamil (Global Education Journal, 2025)
The implementation of the Rantang Simpati policy in North Sumedang District, Sumedang Regency, has not been optimal, despite being regulated by Sumedang Regent Regulation Number 13 of 2020. This study aims to analyze the implementation of the Rantang Simpati program and identify supporting and inhibiting factors. The study used a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation studies. Informants included sub-district officials, village heads, the Family Welfare Movement (TP PKK) program administrators, and beneficiaries. Data analysis was conducted using an interactive model that included data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of the Rantang Simpati program policy has not been optimal, characterized by weak socialization, limited resources, low commitment among implementers, and the absence of written operational procedures (SOPs). Therefore, strengthening policy communication, increasing resources, and improving bureaucratic coordination are needed.